Sixth Method as a Simplified Measurement for SMEs? - Veronika Solilová; Danuše Nerudová (European Financial and Accounting Journal, 2015)
In December 2014, OECD issued a Discussion Draft on Transfer Pricing aspects of cross-border commodity transactions through BEPS action 10, where the adoption of the sixth method in the form of the quoted commodity price and its adjustments were primarily driven as a starting point for transfer pricing purpose. In this paper the analysis of the proposed sixth method and the experience with the sixth method in Argentina were used for the consideration whether this method can be used as simplified measurement for SMEs. SMEs are facing tax obstacles mainly in the area of the international taxation which impede in cross border transactions and internationalization of SMEs. One of tax obstacles represent transfer pricing. Its costs can be disproportionately large for SMEs in comparison to LSEs. Moreover, SMEs are not able to bear the high administrative burden to comply with the transfer pricing rules as they do not posses the sufficient human and economic capital. Based on the results of the research, we can concluded, that there are a lot of questions related to the proposed sixth method, notwitstanding, it has a potential to be a new method for SMEs for they need to face lower tax administrative burden in the area of transfer pricing issues.
Keywords: H25; H26; 650; Sixth method; SMEs; Transfer pricing; Simplified measurements; BEPS